(3GdJhKjb GdUMaj h GdEPGYj h GdJdjaRjhfj (B/s - (3bfOjd, eMeO Ydj CHh GdYdGs ((3GdLRGFQ(B;(3GdLRGFQ (B:s (3OGQ GdYde h GdEjeGf ddfTQ h GdJhRjY(B;(3OGQ GdLOjO ddfTQ h GdJhRjY ,s, 2021)
(3JYQjaGJ HGdJhKjb GdEYdGej h GfhGYg(B- (3JYQja eLJeY GdeYdheGJ h fTCJg h JWhQg GeG aj GdaUd GdKGdK GdJhKjb GdEYdGej aj GdUMGaI h GdEPGYI h GdJdaRjhf h aj GdaUd GdQGHY GdfTQ GdecJHj h GdfTQ GdEdcJQhfj h GNjQG UfGYI GdeYdheGJ hGbY fXGe GdeYdheGJ GdYQHj GdhGbY h GdeCehds
(3HHdjhZQGajG (B: 155-161s
Keywords: (3GdEPGYIs; (3GdJhKjb GdUMaj s; (3GdUMGaIs; (3hSGFd GdEYdGe s